2020
DOI: 10.1111/add.15069
|View full text |Cite
|
Sign up to set email alerts
|

The unique nature of public stigma toward non‐medical prescription opioid use and dependence: a national study

Abstract: Background and Aims Our ability to combat the opioid epidemic depends, in part, on dismantling the stigma that surrounds drug use. However, this epidemic has been unique and, to date, we have not understood the nature of public prejudices associated with it. Here, we examine the nature and magnitude of public stigma toward prescription opioid use disorder (OUD) using the only nationally representative data available on this topic. Design General Social Survey (GSS), a cross‐sectional, nationally representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(112 citation statements)
references
References 21 publications
1
111
0
Order By: Relevance
“…We also considered causal beliefs as 1 aspect of onset responsibility when “bad character” was included as 1 option to explain the origin for a disease (compared to options like “chemistry in the brain” or “stress” or “genetic”), which was the case in 6 studies (see Appendices S6, S7; Andersson & Harkness, 2018; Meurk, Partridge, et al 2014; Hing et al 2016; Meurk, Carter, et al 2014). Compared to vignettes describing persons with depression or schizophrenia, descriptions of persons with AUD tended to be more likely to be associated with a bad character (see Appendices S6, S7; Andersson & Harkness, 2018; Hing et al 2016; Perry et al 2020). Compared to persons with AUD, people with other SUDs or with problem gambling behavior were not considerably different with regard to the public attribution of a “bad character” (Hing et al, 2016; Meurk et al, 2014a, 2014b) or moral weakness (DePierre et al, 2014), with the exception of 2018 US study (AUD: 70.3%, SUD: 52.0%; Perry et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also considered causal beliefs as 1 aspect of onset responsibility when “bad character” was included as 1 option to explain the origin for a disease (compared to options like “chemistry in the brain” or “stress” or “genetic”), which was the case in 6 studies (see Appendices S6, S7; Andersson & Harkness, 2018; Meurk, Partridge, et al 2014; Hing et al 2016; Meurk, Carter, et al 2014). Compared to vignettes describing persons with depression or schizophrenia, descriptions of persons with AUD tended to be more likely to be associated with a bad character (see Appendices S6, S7; Andersson & Harkness, 2018; Hing et al 2016; Perry et al 2020). Compared to persons with AUD, people with other SUDs or with problem gambling behavior were not considerably different with regard to the public attribution of a “bad character” (Hing et al, 2016; Meurk et al, 2014a, 2014b) or moral weakness (DePierre et al, 2014), with the exception of 2018 US study (AUD: 70.3%, SUD: 52.0%; Perry et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies included questions on the desire for social distance themselves from persons with AUD and other mental health conditions, with 10 studies reporting findings relevant to the research question of this systematic review (no information was available for study #2 and study #13). Among studies comparing the desire for social distance from people with AUD to schizophrenia and depression (6 studies), results indicated a greater desire for social distance in the case of AUD compared to depression (significant in study #12; see Appendix ; Andersson & Harkness, 2018; Angermeyer et al 2013; Hengartner et al 2013; Lee & Seo, 2018; Perry et al 2020; Subramaniam et al 2017). With regard to schizophrenia, however, results were less clear, with 2 studies finding a significantly lower desire for social distance in schizophrenia compared to AUD and 5 studies that identified no marked difference (see Appendix ; Andersson & Harkness, 2018; Angermeyer et al 2013; Lee & Seo, 2018; Perry et al 2020; Subramaniam et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the social stigma surrounding naloxone usage and opioid use disorder may prevent someone from trying to obtain naloxone for themselves or for emergencies for others. 8,9 Additionally, media coverage in uences the public opinion of naloxone. 33 This may mean that pharmacists' perceptions of naloxone distribution are skewed, and would therefore directly impact the potential availability of naloxone at independent pharmacies as well as the depth and breadth of counseling provided by those respective pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, barriers to naloxone access are common due to issues such as expense, 6 , lack of awareness, lack of education, 7 and stigma. 8,9 . Many studies have found that increased public awareness and increased pharmacist knowledge and training would be bene cial for increasing access to naloxone and potentially reducing opioid-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Perry et al . [1] have it right! The stigma of opioid use disorder (OUD) and other substance use disorders (SUDs) harms people with these disorders, significantly worsening the course of the disorder.…”
mentioning
confidence: 99%